Yearbook of Chinese theology 2016 - Huang, Baoluo. (Yearbook of Chinese Theology, 2016)
The Yearbook of Chinese Theology is an international, ecumenical and fully peer-reviewed annual that covers Chinese Christianity in the areas of Biblical Studies, Church History, Systematic Theology, Practical Theology, and Comparative Religions. It offers genuine Chinese theological research previously unavailable in English, by top scholars in the study of Christianity in China. The 2016 volume highlights the five sub-disciplines of theology. Wang Wei-fan's evangelical theology and Christian ecumenism and its internal contradiction is studied from a systematic theological viewpoint. Additionally, a theology of soul and body is proposed as an approach of sinicization of Christianity. Civil Christian and political identity are also studied in the relation to the sinicization of Christianity in China. The belief logic and social actions of the "Kingdom-Got sect" and the origin of "A New Treatise on Aids to Administration" have been explored from the historical perspective. The meditations of the Three-Self Church by K. H. Ting from a socio-religious perspective, and the missionaries' resolution of the term question in The Chinese Recorder have been studied in their relations to the Bible. There are comparative studies on the unreconciled religious diversity in the dialogue of civilizations and the different views about truth in Christianity and Confucianism. The academic report analyzes the eventful year of 2010 in the Catholic Church in China. This volume offers genuine Chinese theological research, which was previously unavailable in English, by top scholars in the study of Christianity in China. Contributors include: Juhong Ai, Jianming Chen and Tao Xiao, Xiaojuan Cheng, Xiangping Li, Gong Liang, Jianbo Huang, Paulos Huang, Meixiu Wang, Philip L. Wickeri, Kevin Xiyi Yao, Jie Zhao, Weichi Zhou.